2021
DOI: 10.1016/j.jstrokecerebrovasdis.2021.105985
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown Effects on Acute Stroke Care in Latin America

Abstract: on behalf of Latin American Stroke rEgistry (LASE) COVID-19 Collaborators.Objectives: COVID-19 pandemic has forced important changes in health care worldwide. Stroke care networks have been affected, especially during peak periods. We assessed the impact of the pandemic and lockdowns in stroke admissions and care in Latin America. Materials and Methods: A multinational study (7 countries, 18 centers) of patients admitted during the pandemic outbreak (March-June 2020). Comparisons were made with the same period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
(17 reference statements)
1
11
0
1
Order By: Relevance
“… 10 In addition, a multinational study comprising 7 countries and 18 centers in Latin America showed that there was a mild decrease in admissions of ischemic stroke during the COVID-19 lockdown period (March-June 2020) compared to the same period in 2019, with a significant delay in time to consultations and worse hospitalization outcomes. 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 In addition, a multinational study comprising 7 countries and 18 centers in Latin America showed that there was a mild decrease in admissions of ischemic stroke during the COVID-19 lockdown period (March-June 2020) compared to the same period in 2019, with a significant delay in time to consultations and worse hospitalization outcomes. 11 …”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, a multinational study comprising 7 countries and 18 centers in Latin America showed that there was a mild decrease in admissions of ischemic stroke during the COVID-19 lockdown period (March-June 2020) compared to the same period in 2019, with a significant delay in time to consultations and worse hospitalization outcomes. 11 Government instructions involving stay-at-home, lockdown, curfew, and social distancing policies have proved effective in combating the COVID-19 dissemination. [12][13][14] However, social distancing during the COVID-19 period lockdown may also play a central role in the delays of ischemic stroke patient referrals and escalated treatment to tertiary centers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study evidenced a substantial increase in the proportion of stroke admissions beyond 48 h from symptoms onset. Therefore, it is possible that the delay in diagnosis and treatment of stroke, demonstrated by a larger time to consultation during lockdown period, may have contributed to an increase in mortality [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding public health data in Latin America, there has been a decrease in non-COVID-19–related healthcare during lockdown. This includes the suspension of nontransmissible diseases and mental health primary care services 19 and a reduction in stroke consultations in emergency rooms, 20 together with decreases in cancer screening tests and therapies (chemotherapy and oncologic surgery). 21…”
Section: Covid-19 Pandemic In Latin America: Effects Of Poverty and S...mentioning
confidence: 99%